PENGARUH LIKUIDITAS, LEVERAGE, INVENTORY TURNOVER, DAN DIVIDEND PAYOUT RATIO TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL (Studi Pada Perusahaan Property & Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020) - Bella Arditya; Prasetiono Prasetiono (Diponegoro Journal of Management, 2023)
ABSTRACT This research examined the effect of liquidity, leverage, inventory turnover, and dividend payout ratio on firm value with firm size as control variable. Firm value is measured using the price to book value. The research used secondary data and the population of this research was 160 property & real estate companies listed on the Indonesia Stock Exchange in the 2016-2020 period. The method used by purposive sampling with 35 property & real estate firm were obtained as the sample of this research. The analytical method used multiple linear regression analysis. The results showed that liquidity, leverage, and inventory turnover have a positive and significant effect on firm value, and dividend payout ratio has a negative and significant effect on firm value.